2019
DOI: 10.1152/ajpendo.00098.2019
|View full text |Cite
|
Sign up to set email alerts
|

Sex modulates hepatic mitochondrial adaptations to high-fat diet and physical activity

Abstract: The impact of sexual dimorphism and mitophagy on hepatic mitochondrial adaptations during the treatment of steatosis with physical activity are largely unknown. Here, we tested if deficiencies in liver-specific peroxisome proliferative activated-receptor-γ coactivator-1α (PGC-1α), a transcriptional coactivator of biogenesis, and BCL-2/ADENOVIRUS EIB 19-kDa interacting protein (BNIP3), a mitophagy regulator, would impact hepatic mitochondrial adaptations (respiratory capacity, H2O2 production, mitophagy) to a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 65 publications
14
51
1
Order By: Relevance
“…In line with increased liver PGC-1α being beneficial in NAFLD, liver-specific overexpression of PGC-1α in Sprague Dawley male rats increases fatty acid oxidation and tricarboxylic acid (TCA) cycle activity in isolated liver mitochondria, and this was coupled with reduced hepatic and plasma triglycerides [73]. While hepatic PGC-1α is known to increase in a fasting liver to promote lipid catabolism, it is interesting to note that it also increases following acute exercise training in rodents [74,75,76,77]. McCoin et al investigated whether liver-specific hemizygous disruption of PGC-1α had an impact on hepatic mitochondrial adaptation (respiratory capacity, H 2 O 2 production, mitophagy) in male and female mice fed a high-fat diet (HFD) and whether exercise (voluntary wheel running) affected outcomes [77].…”
Section: Mitochondrial Dysfunction In Non-alcoholic Steatohepatitimentioning
confidence: 99%
See 1 more Smart Citation
“…In line with increased liver PGC-1α being beneficial in NAFLD, liver-specific overexpression of PGC-1α in Sprague Dawley male rats increases fatty acid oxidation and tricarboxylic acid (TCA) cycle activity in isolated liver mitochondria, and this was coupled with reduced hepatic and plasma triglycerides [73]. While hepatic PGC-1α is known to increase in a fasting liver to promote lipid catabolism, it is interesting to note that it also increases following acute exercise training in rodents [74,75,76,77]. McCoin et al investigated whether liver-specific hemizygous disruption of PGC-1α had an impact on hepatic mitochondrial adaptation (respiratory capacity, H 2 O 2 production, mitophagy) in male and female mice fed a high-fat diet (HFD) and whether exercise (voluntary wheel running) affected outcomes [77].…”
Section: Mitochondrial Dysfunction In Non-alcoholic Steatohepatitimentioning
confidence: 99%
“…While hepatic PGC-1α is known to increase in a fasting liver to promote lipid catabolism, it is interesting to note that it also increases following acute exercise training in rodents [74,75,76,77]. McCoin et al investigated whether liver-specific hemizygous disruption of PGC-1α had an impact on hepatic mitochondrial adaptation (respiratory capacity, H 2 O 2 production, mitophagy) in male and female mice fed a high-fat diet (HFD) and whether exercise (voluntary wheel running) affected outcomes [77]. They note wild-type female mice have an inherent ability to increase hepatic mitochondrial function in response to the obesogenic challenge, while males need exercise to equally adapt their respiratory capacity.…”
Section: Mitochondrial Dysfunction In Non-alcoholic Steatohepatitimentioning
confidence: 99%
“… 5 To this end, our group and others have shown that defects in mitochondrial quality control pathways, such as mitophagy (the targeted degradation of damaged mitochondria), increase the susceptibility to hepatic steatosis in preclinical rodent models. 6–9 While we have shown that treatments such as exercise can alter mitophagy and mitochondrial respiratory function during high-fat feeding, 9 alternative strategies that improve hepatic mitochondrial quality control and function and ameliorate steatosis are needed as contraindications can exist for exercise in certain patient populations. 10 One potential strategy that our group has explored to great effect in animals and primary hepatocytes is heat treatment (HT).…”
Section: Introductionmentioning
confidence: 99%
“…For all other complexes, neither TAM nor EWD treatment impacted protein content in either diet group (Supplemental Fig 3G-H). These data suggest that the liver phenotype observed in HFHS mice treated with TAM or EWD is not the product of direct action of TAM or EWD on hepatic mitochondria after 7 weeks of treatment; however, disruption of ER signaling is known to directly impact the liver in several studies 48,49 .…”
Section: Increased Hepatic Steatosis and Altered Hepatic Metabolism Wmentioning
confidence: 87%